ANALYSING CRIMES AGAINST CHILDREN IN INDIA: A FOCUS ON UTTAR PRADESH IN 2019 (International Journal of Food and Nutritional Sciences, 2022)
This paper provides a comprehensive analysis of crimes against children in India, focusing particularly on the state of Uttar Pradesh (UP), based on the secondary data extracted from National Crime Records Bureau (NCRB). The collected data is tabulated and analysed by the author for the status comparison of state Uttar Pradesh. The analysis encompasses various categories of crimes, including murder, kidnapping and abduction, assault on children, actions taken by police and courts, age and gender distribution of victims, and the relationship between perpetrators and victims under the Protection of Children from Sexual Offences (POCSO) Act. The data reveals significant disparities between India and UP, highlighting the urgent need for targeted interventions and policy measures to address the underlying factors contributing to these offenses. The findings underscore the importance of region-specific strategies to enhance law enforcement, improve judicial processes, and strengthen community engagement in safeguarding children's rights and well-being. Ultimately, the paper emphasizes the importance of a comprehensive, multi-sectoral approach to prevent crimes against children and create safer environments for their growth and development.